2006
DOI: 10.1007/s11664-006-0253-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cd1−xZnxTe crystals grown from a modified vertical bridgman technique

Abstract: Cd 1ÿ x Zn x Te (CZT) crystals grown from a modified vertical Bridgman technique were characterized by means of an optical polarized transmission technique using the Pockels effect, low-temperature direct current (DC) photoconductivity technique, low-temperature photoluminescence (PL) spectroscopy, room-temperature PL mapping technique, and detector performance measurements. Electric field mapping indicates that an approximation of a uniform electric field distribution approximation is generally satisfied for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…In this work, we studied CdMnTe crystals grown by modified low-pressure Bridgman (MLPB) technique at Yinnel Tech [13]. Infrared (IR) microscopy was used to screen the crystals for the presence of defects, specifically twins and Te inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we studied CdMnTe crystals grown by modified low-pressure Bridgman (MLPB) technique at Yinnel Tech [13]. Infrared (IR) microscopy was used to screen the crystals for the presence of defects, specifically twins and Te inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…The above (mt) e values extracted with different sources are in reasonably good agreement with each other. The shaping time for 5.5 MeV source was 4 ms, while for all g sources the shaping used was 1 ms. Y. Cui et al [18] also reported similar (mt) e values obtained with different excitations like photo current, alpha source, and 59.6 and 662 keV gamma sources. The (mt) e value obtained from other samples from the same ingot were in the range 4-7 Â 10 À 3 cm 2 /V.…”
Section: Resultsmentioning
confidence: 63%
“…The need for high-purity cadmium-zinc-telluride (CZT) crystals for high-resolution radiation detection is well documented and many research groups are engaged in crystal growth of CZT [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], in fabrication of gamma-ray detectors from CZT [15,[17][18][19][20][21][22][23], and in the design of detector systems based on CZT [18,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. A ubiquitous problem for CZT crystals is the unwanted incorporation of Te-particles or Teprecipitates within the CZT crystal during the crystal growth process, in addition to other crystal defects.…”
Section: Introductionmentioning
confidence: 99%